Assessment of Gas Adsorption Capacity in Shale Gas Reservoirs - Zou, Jie (Curtin University, 2019)
A study into potential gas shales is conducted to define the controlling factors of gas adsorption and evaluate gas adsorption capacity in shale gas reservoirs. The results from high-pressure adsorption experiment show that temperature, moisture and composition affect the gas adsorption in shale. In this study, a tool is introduced to predict gas adsorption capacity. This study helps to understand the mechanism of gas adsorption and evaluate gas storage in shale gas reservoirs.